Cloud‐based performance management of community care services. Issue 7 (7th September 2017) - Eze, Benjamin; Kuziemsky, Craig; Peyton, Liam
Abstract: Triple Aim for connected care is about improving patient experience, improving population health, and lowering cost of care. One of the key challenges to operationalizing Triple Aim is our ability to measure improvements at all levels of the health care ecosystem especially with respect to connected care. With a lack of interoperability between stakeholders in the health care system, our ability to measure quality of care goals is limited. Cloud computing offers the potential to improve data sharing and interoperability, thereby providing a good framework for operationalizing Triple Aim. In this paper, we evaluate our systematic framework for performance management of community care services based on a successful implementation for a large urban health region in support of Triple Aim. Three critical roadblocks to interoperability in a cloud computing context are identified (infrastructure, common data model, and a compliance framework), and alternative approaches to addressing them are evaluated and discussed. Abstract : In this paper, we analyze a case study to provide a systematic framework for performance management of community care across a large urban health region in support of Triple Aim. Figure 1A depicts the system before the case study with minimal interoperability and limited ability to do performance management. Figure 1B shows the cloud‐based framework for performance management services (data hosting, data collection, reporting and analysis, and subscription services) that has been implemented for community support services agencies and the community home care delivery.